External financial control in the Russian Federation: the essence and legal framework - V. K Khomushku (Вестник университета)
The genesis of the essence and foundations of the legal regulation of financial control in Russia since the market reforms of the 1990s and to the present time has been considered. The current regulatory framework and general characteristics of the system of external state and municipal financial control in the Russian Federation have been introduced. The main provisions of the Federal law dated 7 February 2011 No 6-FZ «On general principles of organization and activity of control and accounting bodies of the Russian Federation and municipalities» have been considered. The main tasks, remaining at the present stage of development of the system of state financial control in the Russian Federation have been disclosed.